2021
DOI: 10.3390/polym13213678
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Polytetrafluoroethylene Modified by the Combined Action of γ-Radiation and High Temperatures

Abstract: By means of X-ray computed microtomography (XCMT), the existence of a developed porous structure with an average pore diameter of ~3.5 μm and pore content of ~1.1 vol.% has been revealed in unirradiated polytetrafluoroethylene (PTFE). It has been found that the combined action of gamma radiation (absorbed dose per PTFE of ~170 kGy) and high temperatures (327–350 °C) leads to the disappearance of the porous structure and the formation of several large pores with sizes from 30 to 50 μm in the bulk of thermal-rad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 71 publications
(160 reference statements)
2
10
0
Order By: Relevance
“…It should also be noted that when the gamma radiation energy increases, the RPE rates decrease, meaning that these decreases in the RPE rates confirm that all of our results are compatible with the other attenuation parameters (i.e., , , HVL, TVL, MFP) computed and experimentally detected. These conclusions obtained are consistent with the results of the research composites developed for gamma-ray shielding with various nanostructured additives, including polymers [ 11 , 12 , 30 , 31 , 32 , 33 ]. As a result, the current alterations in nanoparticle proportions are quite efficacious for diminishing the influence of gamma radiation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It should also be noted that when the gamma radiation energy increases, the RPE rates decrease, meaning that these decreases in the RPE rates confirm that all of our results are compatible with the other attenuation parameters (i.e., , , HVL, TVL, MFP) computed and experimentally detected. These conclusions obtained are consistent with the results of the research composites developed for gamma-ray shielding with various nanostructured additives, including polymers [ 11 , 12 , 30 , 31 , 32 , 33 ]. As a result, the current alterations in nanoparticle proportions are quite efficacious for diminishing the influence of gamma radiation.…”
Section: Resultssupporting
confidence: 90%
“…Doyan et al worked on the polymeric film materials of polyvinyl alcohol (PVA), trichloroethylene (TCE), and cresol red (CR) dye to expose the gamma beams for eventual implementation in radiation dosimetry; their results indicate that enhancement of the radiation rate altered the hue of the polymeric film, from purple (pH > 8.8) with no radiation (0 kGy) to yellow (nearly pellucid) (2.8 < pH < 7.2) at the uppermost rate (12 kGy); in other words, these results demonstrated a useful dose range of 0–12 kGy for the investigated polymeric film samples [ 31 ]. Smolyanskii et al worked on the construction of polytetrafluoroethylene developed via the combination of gamma irradiation and high temperatures, and concluded that these conditions (327–350 °C) lead to the evanescence of the poriferous texture and the creation of a few large pores [ 32 ]; furthermore, they indicated that it is important to carry out new research on the continuity of changes in the structure and irradiation–chemical operations, depending on the irradiation temperature. A. Abu Saleem et al focused on the shielding properties of epoxy + carbon- and glass-fiber composites doped with lead nanoparticles [ 33 ]; their conclusions indicate that the values rise as lead nanoparticle rates increase up to a specific proportion (~15 wt%), after which the enhancement in the values becomes negligible.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the detected effect of a significant deterioration of the hydrogen permeability of TRM-PTFE films may be associated with the elimination of the micropore system as a result of the combined action of γ-irradiation and high temperatures [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The irradiation temperature varied from 323 to 350 °C, nitrogen was used as the external medium, irradiation was carried out at a dose of 50 kGy at a dose rate of ~3 Gy/s. Corrections for the difference between the electron densities of the Fricke dosimeter and PTFE were taken into account during the radiation treatment (the absorbed dose conversion factor for PTFE was 0.87 [ 23 ]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation